A Community-Based Approach to Blood Glucose Control in Type 2 Diabetes: Diabetes Exercise and Health Education - Umi Margi Rahayu; Kholis Khoirul Huda; Mardiyono (STIKes Patria Husada Blitar, 2025)
Type II diabetes mellitus is a chronic disease that often leads to serious complications, especially when blood glucose levels are not well controlled. Blood glucose reduction can be achieved through various interventions, one of which is diabetes exercise combined with health education. This study aimed to evaluate the effect of diabetes exercise and health education on blood glucose levels and knowledge of patients with type II diabetes mellitus. The method used was a community service activity involving 60 respondents at Srondol Public Health Center, Semarang City. The program consisted of diabetes exercise sessions and health education on diabetes management. The results showed a significant decrease in blood glucose levels before and after the exercise intervention. In addition, there was an increase in respondents' knowledge regarding diabetes management after receiving health education. The Focus Group Discussion (FGD) revealed that respondents felt more motivated and experienced strong social support in managing their diabetes. In conclusion, diabetes exercise and health education were proven to be effective in reducing blood glucose levels and improving patients' knowledge of diabetes management. This program can be widely implemented in the community to support sustainable diabetes control.